Special educational needs and disabilities in schools a critical introduction - Wearmouth, Janice (Bloomsbury Academic, 2017)
"Special Educational Needs and Disabilities in Schools is a key resource in supporting student teachers during and beyond their teaching training to begin to understand how, and be able, to address the needs of children and young people within schools and college in line with the Code of Practice (DfE, 2014). Drawing on her wealth of experience and up-to-date theory, Janice Wearmouth, explores current legislation related to special educational needs and disability (SEND) within a historical and geographical context so that readers can understand how and why the current SEND policy and practice has developed as it has. She considers assessment and planning in relation to both informal and standardised approaches, and offers ways to engage with young people's, peers' and families' views and experiences. Wearmouth focuses on ways to understand, assess and address the most common forms of SEND: literacy and numeracy difficulties and behavioural concerns related to social, emotional and mental health. She discusses how ICT might be used to include young people with various degrees of difficulty in learning and explores professional relationships and partnership work with parents and families. Throughout this engaging guide, readers are supported with clear questions of focus for each chapter, and within each chapter exemplars and vignettes, and reflective and discussion activities for individuals and groups, can be found to enable them to consider their own practice to ensure that all young people can learn effectively in their classrooms. The supportive companion website provides a wealth of additional material, including reflective activities, examples of different kinds of assessment tools and interventions, check lists, examples of school/college policy documents, and classroom and individual student observation tools and templates for understanding and assessing difficult behaviour and planning for improvement."--Provided by publisher.